KECENDERUNGAN HUBUNGAN ANGGOTA LEGISLATIF DAN KONSTITUEN : Studi DPRD Provinsi Banten Hasil Pemilu 2009 - Luky Sandra Amalia (Jurnal Penelitian Politik, 2011)
This research report is about relations ofMember ofParliament and his her constituent in Banten ProvinceThe MPs are those who elected by General Election 2009 One ofthe reasons behind this study is critics towards MPs who does not perform their duty optimally Because of that MPs does not have close relations with his herown constituent This study suggests some evaluation to the current condition